[Aerial View of Poly Ninos Housing] (1953)
View of Poly Ninos (Vetville), Agricultural Engineering, Poly Canyon, North Mountain Dorms - looking east. Aerial view of Agricultural Engineering Buildings - looking east to northeast side of campus. Also visible is the Corporation yard, Welding, Thoroughbred Horse Unit (aka Mare Barn) in upper right corner (before it was moved). Also see the Feed Mill and Meat Lab and Steer Feed lot in upper left corner. Taken at same time as this photo: https://digital.lib.calpoly.edu/rekl-5443